An Ethnographic Contribution to a Look at Jerusalemʼs Axis Mundi (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
The article examines the concept of Jerusalem as an axis mundi, or world axis, in an ethnographic context. It utilizes cultural analysis and the findings of its own ethnographic observations to delve into various aspects of viewing Jerusalem as a central point of the world in different cultures and religions. It presents various perspectives of local communities and pilgrims, illustrating how Jerusalem is perceived and interpreted by different religious groups. The article demonstrates how the axis mundi manifests in Jerusalem and the implications this has for understanding the religious and cultural dimensions of the city.